Schistosome Satellite DNA Encodes Active Hammerhead Ribozymes - Ferbeyre, Gerardo (American Society for Microbiology, 1998)
Using a computer program designed to search for RNA structural motifs in sequence databases, we have found a hammerhead ribozyme domain encoded in the Smα repetitive DNA of Schistosoma mansoni. Transcripts of these repeats are expressed as long multimeric precursor RNAs that cleave in vitro and in vivo into unit-length fragments. This RNA domain is able to engage in both cis and trans cleavage typical of the hammerhead ribozyme. Further computer analysis of S. mansoni DNA identified a potential trans cleavage site in the gene coding for a synaptobrevin-like protein, and RNA transcribed from this gene was efficiently cleaved by the Smα ribozyme in vitro. Similar families of repeats containing the hammerhead domain were found in the closely related Schistosoma haematobium and Schistosomatium douthitti species but were not present in Schistosoma japonicum or Heterobilharzia americana, suggesting that the hammerhead domain was not acquired from a common schistosome ancestor.